Nomogram for Predicting Occult Locally Advanced Esophageal Squamous Cell Carcinoma Before Surgery - Huang, Zhixin; Hong, Zhinuan; Chen, Ling; Kang, Mingqiang (Frontiers in Surgery, 2022)
Introduction The limitations of preoperative examination result in locally advanced esophageal squamous cell carcinoma (ESCC) often going undetected preoperatively. This study aimed to develop a clinical tool for identifying patients at high risk for occult locally advanced ESCC; the tool can be supplemented with preoperative examination to improve the reliability of preoperative staging. Materials and Methods Data of 598 patients who underwent radical resection of ESCC from 2010 to 2017 were analyzed. Logistic multivariate analysis was used to develop a nomogram. The training cohort included patients who underwent surgery during an earlier period (n = 426), and the validation cohort included those who underwent surgery thereafter (n = 172), to confirm the model’s performance. Nomogram discrimination and calibration were evaluated using Harrell's concordance index (C-index) and calibration plots, respectively. Results Logistic multivariate analysis suggested that higher preoperative carcinoembryonic antigen levels (>2.43, odds ratio [OR]: 2.093; 95% confidence interval [CI], 1.233–2.554; P = 0.006), presence of preoperative symptoms (OR: 2.737; 95% CI, 1.194–6.277; P = 0.017), presence of lymph node enlargement (OR: 2.100; 95% CI, 1.243–3.550; P = 0.006), and advanced gross aspect (OR: 13.103; 95% CI, 7.689–23.330; P < 0.001) were independent predictors of occult locally advanced ESCC. Based on these predictive factors, a nomogram was developed. The C-indices of the training and validation cohorts were 0.827 and 0.897, respectively, indicating that the model had a good predictive performance. To evaluate the accuracy of the model, we divided patients into high-risk and low-risk groups according to their nomogram scores, and a comparison was made with histopathological data. Conclusion The nomogram achieved a good preoperative prediction of occult locally advanced ESCC; it can be used to make rational therapeutic choices.